La caricatura de oposición en los congresos de la época de Juárez, 1861-1872 - Arroyo, Israel (Anuario de Historia de América Latina, 2019)
The article analyzes cartoons in the opposition press during the government of Benito Juárez (1861-1872). It focuses on two emblematic newspapers with cartoons of the time: La Orquesta and El Padre Cobos. The study argues that the opposition press should be understood as a creator of a collective imaginary – that could be very distant from political realities –, rather than as political player with a real impact in the political thought of the people. In spite of claiming to represent the people, the Mexican political cartoon actually addressed the public sphere of the press and the political class of its time.